Proceedings of the 2nd Social and Humaniora Research Symposium (SoRes 2019) 2020
DOI: 10.2991/assehr.k.200225.111
|View full text |Cite
|
Sign up to set email alerts
|

English Writing Anxiety and the Writing Problems of Indonesia EFL Learners

Abstract: This descriptive research investigated the level of English writing anxiety experienced by Indonesian EFL students. The respondents were 38 undergraduate students of English Literature program of a university in Semarang Central Java, Indonesia taking Essay Writing course which adopted portfolios as the assessment method. Data were collected by two closed questionnaires; the one was for collecting data of English writing anxiety and the second was for collecting data of writing problems faced by students which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
(25 reference statements)
2
9
0
Order By: Relevance
“…In our study, it was also found that procrastination was prevalent among the students as stated earlier so the students may have developed anxiety due to writing essays (Onwuegbuzie, 2004;Klassen et al, 2008). Writing anxiety negatively affects writing performance and motivation, whereas it positively correlates with academic procrastination (Hartono & Maharani, 2019).…”
Section: Findings and Discussionsupporting
confidence: 76%
“…In our study, it was also found that procrastination was prevalent among the students as stated earlier so the students may have developed anxiety due to writing essays (Onwuegbuzie, 2004;Klassen et al, 2008). Writing anxiety negatively affects writing performance and motivation, whereas it positively correlates with academic procrastination (Hartono & Maharani, 2019).…”
Section: Findings and Discussionsupporting
confidence: 76%
“…In terms of gender, male teachers felt more anxious than female teacher selfperception of language proficiency, fear of evaluation, inexperience, and time management, while the younger teacher worried the older one in terms of perceiving target language skills and fear of making mistakes (p. 865, Aydin and Uştuk (2020)). Whereas the fourth related previous study was conducted by Hartono and Maharani (2020). It was about English writing anxiety and the writing problems of Indonesia EFL learners.…”
Section: Foreign Language Teaching Anxiety (Flta)mentioning
confidence: 99%
“…Meanwhile, good method might have been applied by the teacher in teaching procedure text writing. In another study involving 38 undergraduate EFL students discovered that students had high level of anxiety in English writing, with cognitive anxiety being the most suffered by the students [15]. Neither gender nor the perception of writing difficulties gave any impact to the level of anxiety.…”
Section: Introductionmentioning
confidence: 97%